2020
DOI: 10.1016/j.smim.2020.101390
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in tumor associated carbohydrate antigen based chimeric antigen receptor T cells and bispecific antibodies for anti-cancer immunotherapy

Abstract: Tumor associated carbohydrate antigens (TACAs) are a class of attractive antigens for the development of anti-cancer immunotherapy. Besides monoclonal antibodies and vaccines, chimeric antigen receptor (CAR) T cells and bispecific antibodies (BsAbs) targeting TACA are exciting directions to harness the power of the immune system to fight cancer. In this review, we focus on two TACAs, i.e., the GD2 ganglioside and the mucin-1 (MUC1) protein. The latest advances in CAR T cells and bispecific antibodies targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…On many epithelial-origin cancer cells, MUC1 is enriched by specific tumor-associated carbohydrate antigens (TACAs), including Tn, T, sTn, and sT sugar structures. They are overexpressed on the surface of cancer cells compared to those on normal tissues [ 49 ]. It has been reported that the presence of such truncated glycan structures plays a key role in tumor initiation, progression, and metastasis as TACAs are able to interact with many factors participating in signaling pathways promoting cancer development (leading to the creation of a pro-tumor microenvironment, favoring tumor progression and metastasis) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On many epithelial-origin cancer cells, MUC1 is enriched by specific tumor-associated carbohydrate antigens (TACAs), including Tn, T, sTn, and sT sugar structures. They are overexpressed on the surface of cancer cells compared to those on normal tissues [ 49 ]. It has been reported that the presence of such truncated glycan structures plays a key role in tumor initiation, progression, and metastasis as TACAs are able to interact with many factors participating in signaling pathways promoting cancer development (leading to the creation of a pro-tumor microenvironment, favoring tumor progression and metastasis) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…TACAs expression levels have been used as biomarkers of poor prognosis [ 51 ]. Moreover, they have been recently proposed as a specific “glycol-code” that could be considered as a novel immune checkpoint, offering new immunotherapeutic opportunities [ 49 , 50 ]. In our study, we assumed that anti-MUC1 based therapy could also block MUC1 associated TACAs expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although anti-GD2 monoclonal antibodies have been successful in treating patients with NB metastases in their bone marrow, this approach has not been beneficial as a single agent against patients with substantial and wide-spread disease (Sait & Modak, 2017). CAR T-cells have the potential for increased potency and durability compared with mAbs and it may in the future overcome this challenge to effective therapeutic outcomes in patients (Rashidijahanabad & Huang, 2020).…”
Section: Immune Therapymentioning
confidence: 99%
“…In addition, while antibodies generally do not penetrate the CNS (Rashidijahanabad & Huang, 2020), CAR-T cells can cross the blood-brain barrier (Iwasaki, 2017;Pule et al, 2008). Reverted NB of the CNS has emerged as a clinical entity since the adoption of anti-GD2 monoclonal antibodies, and CARs may provide an answer to this challenging clinical problem (Lammie et al, 1993;Sait & Modak, 2017).…”
Section: Immune Therapymentioning
confidence: 99%
“…Disialoganglioside (GD2), an N-acetyl neuraminic acid-containing glycolipid antigen, is composed of five monosaccharides anchored to the lipid bilayer of the plasma membrane through a ceramide lipid [35]. GD2 expression is low in normal tissues [36] but high in solid tumors in children and adults, including neuroblastomas, Ewing's sarcoma, and OS [63].…”
Section: Disialoganglioside (Gd2)mentioning
confidence: 99%